Kearifan Kaenbaun sebagai dasar konseptual pada tata spasial arsitektur permukiman suku Dawan di desa Kaenbaun - Sudaryono; Yohanes Djarot Purbadi; Achmad Djunaedi (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2019)
The Research based on an intercultural contact approach is significant to study the traditional settlements and to support the preservation of local culture-based architecture in Indonesia. The Kaenbaun village inhabited by Dawan tribes is a vernacular village and organized based on local resources (physical-natural, technological, economic, social and cultural) fully. It is believed that even the ancestral spirits were involved in structuring settlements and the process of village life. The Kaenbaun's culture is a mixture of Dawan culture and the faith and dogma of the Catholic church which form Kaenbaun's wisdom and underlie the behavior of citizens and the spatial layout of Kaenbaun's settlements. The study was conducted by using field observation guided by Husserlian phenomenological paradigm. The data were processed based on inductive-qualitative thinking by using the field notes taken from field research activities in 2004 to 2010. Data were also supplemented by actual information gathered in 2010-2018 through digital media. The result showed that the local wisdom of Kaenbaun (Kaenbaun's wisdom) emerged from the Dawan culture with the acculturation of Catholic faith and dogma becoming a guideline for the behavior of citizens and the spatial structure of the Kaenbaun village settlement architecture. The Kaenbaun's wisdom is the concept of Kaenbaun's ideal life where humans live in harmony with their fellow humans, harmony with nature, blessed by their ancestors and blessed by God. © 2019 Yohanes Djarot Purbadi, Achmad Djunaedi, Sudaryono